Frontispiece: Single‐Scan 13C Diffusion‐Ordered NMR Spectroscopy of DNP‐Hyperpolarised Substrates. Issue 66 (27th November 2017) - Guduff, Ludmilla; Kurzbach, Dennis; van Heijenoort, Carine; Abergel, Daniel; Dumez, Jean‐Nicolas
Abstract : Dissolution dynamic nuclear polarisation (D‐DNP) provides dramatic signal enhancements for solution‐state NMR. The short‐lived nature of the polarisation in solution, however, makes the acquisition of multidimensional data challenging. Here, using a spatial encoding strategy, spectrally diffusion‐ordered NMR spectroscpy (DOSY) data are acquired in a single scan from DNP‐hyperpolarised substrates. The resulting method has a great potential for the analysis of mixtures. For more information, see the Communication by J.‐N. Dumez et al. onpage 16722 ff.